2022
DOI: 10.3389/fpsyg.2021.791263
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Stress and Growth Among the Children and Adolescents in the Aftermath of COVID-19

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has enkindled many mental health problems across the globe. Prominent among them is the prevalence of post-traumatic stress (PTS) with hosts of its precipitating factors being present in the surrounding. With India witnessing severe impact of the second wave of COVID-19, marked by a large number of hospitalizations, deaths, unemployment, imposition of lockdowns, etc., its repercussions on children and adolescents demand particular attention. This study aims to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…In Zhang et al’s (2020) online study with 3,459 Chinese participants, perceived threat mediated the positive relationship between exposure level and mental health problems. Factors such as media coverage and perceptions of risk can be crucial for mental health ( Blendon et al, 2004 ; Otto et al, 2007 ; Bhushan et al, 2022 ). Liu et al (2020) found the concerns about the threat posed by COVID-19 to life and health was the only significant predictor of somatic symptoms in Chinese primary school children, which is consistent with our results that threat experience was the best predictor of children’s mental health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Zhang et al’s (2020) online study with 3,459 Chinese participants, perceived threat mediated the positive relationship between exposure level and mental health problems. Factors such as media coverage and perceptions of risk can be crucial for mental health ( Blendon et al, 2004 ; Otto et al, 2007 ; Bhushan et al, 2022 ). Liu et al (2020) found the concerns about the threat posed by COVID-19 to life and health was the only significant predictor of somatic symptoms in Chinese primary school children, which is consistent with our results that threat experience was the best predictor of children’s mental health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the growing interest in PTG in the Corona crisis, few studies have examined the phenomenon in non-adults. Although some studies on PTG in adolescents during the COVID-19 pandemic have been conducted ( Bhushan et al, 2022 ; Jian et al, 2022 ; Ulset and von Soest, 2022 ; Zhen and Zhou, 2022 ), research on children is still lacking. Zhen and Zhou (2022) found three heterogeneous patterns characterised by struggle (48.9%), distress (14.8%), and growth (36.3%) in 683 Chinese adolescents (15–18 years old).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, despite the heightened incidence of negative mental health outcomes during the pandemic, some individuals have displayed signs of PTG. The phenomenon of PTG among youths during COVID-19 suggests that with proper support and guidance, young people can adapt to the challenges they faced during the pandemic and even experience positive personal growth [33].…”
Section: Discussionmentioning
confidence: 99%
“…Since losing a parent, especially unexpectedly, can be one of the most life-altering events for a child or adolescent, these numbers are quite significant (Gray et al, 2022). PTG was found in 39.79% of children in one study examining the exhibition of both post-traumatic stress and PTG in children in the aftermath of Covid-19 (Bhushan et al, 2022).…”
Section: Specific Traumatic Events and Ptgmentioning
confidence: 99%